Synthesis and Charecterization of Metal Complexes of 2- [(1-methyl-1H-Tetrazole-5yl) thio]-N’-[(1E)-(4-methyl-1-3-thiazole-5-yl) methylene] acetohydrazide - J. Akilandeswari; S. Joseph Selvaraj; S.R. Bheeter; D. Saravanan (International Journal of Research in Chemistry and Environment (IJRCE), 2017)
The ligand 2-[(1-methyl-1H-Tetrazole-5yl)thio]–N’-[(1E)-4-methyl-1,3-Thiazole-5-yl)methylene] acetohydrazide Was synthesized and the complexes with metal chlorides such as Co(II), Ni(II) and Metal perchlorates of Co(II) were synthesized and charecterized on the basis of IR, and H1 NMR , UV-Visible molar conductivity, Cyclic voltammetric analysis and Magnetic susceptibility Measurements. Spectral data reveal that ligands chealated with metal through N-atoms. Magnetic susceptibility measurements favors octahedral coordination for Co(II), Ni(II) metal complexes.